Micropropagation of Crotalaria laburnifolia L. – An ethnomedicinally important herbal species - Rajender, K; Thirupathi, M; Srinivas, D; Raju, D; Jaganmohan Reddy, K (Journal of Phytology, 2012)
A protocol for in vitro shoot multiplication in Crotalaria labumifolia L. through nodal explants was established. Excision and culture of the nodal segments from in vitro developed shoots on fresh MS medium with concentration of BA (1mg/1) facilitated development of multiple shoots. Subsequent cultures enhanced the rate of shoot proliferation. Shoots cultured on ½ MS medium containing NAA (0.5 mg/1) initiated roots well compared with IBA and this is the most suitable protocol studied in C. labumifolia. The present study is the first report on in vitro regeneration in this species